Improved mechanical performances of unidirectional jute fibre composites developed with new fibre architectures. Issue 37 (29th June 2021) - Hasan, Mahmudul; Saifullah, Abu; Dhakal, Hom N.; Khandaker, Shahjalal; Sarker, Forkan
Abstract : This study detailed two novel processes, the use of stitching and PVA sizing based jute fibre UD preforms, with bamboo slice hybridization for the manufacturing of high-mechanical-performance jute composites, and significant improvement was found. Abstract : This study presents the mechanical performance enhancements of jute fibre composites, manufactured from two newly developed novel jute fibre unidirectional (UD) preforms, namely, stitching-based and sizing-based examples. To increase the use of jute fibres, which are naturally abundant and inexpensive, and to provide research into the use of mechanically advantageous continuous unidirectional (UD) preforms in composites (which are still limited in use), this study employed polyvinyl alcohol (PVA) sizing and stitching techniques, thus increasing the abilities of jute fibres to withstand higher loads and enabling them to be used for lightweight structural applications. Alkali treatment was used on jute fibres in stitched and sized preforms, and bamboo slices were introduced to the jute preforms to further optimize the mechanical properties. The jute composites exhibited significant mechanical property enhancements, with maximum improvement observed in the case of the PVA-sized alkali-treated specimen, thanks to the excellent compatibility between the sized and alkali-treated jute fibres.